2019
DOI: 10.1002/jez.2327
|View full text |Cite
|
Sign up to set email alerts
|

Prior restraint stress inhibits habituation to novel objects in the European starlings (Sturnus vulgaris)

Abstract: Animals often avoid novel objects, a behavior known as neophobia. We examined behavioral responses of captive European starlings to novel objects placed at their food dishes. Exposure occurred concurrently to food reintroduction following overnight fasting. Behavior was analyzed for 10 min via video recording. We expected an increase in avoidance behavior compared with trials in which food was reintroduced without a novel object. Seven of 10 novel objects increased latency to approach the dish. In contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Seven different novel objects were used throughout the study, which all have been shown to elicit neophobic responses in starlings (de Bruijn & Romero, 2020). Each object modified a normal white square plastic feeding dish (100 × 70 × 75 mm).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven different novel objects were used throughout the study, which all have been shown to elicit neophobic responses in starlings (de Bruijn & Romero, 2020). Each object modified a normal white square plastic feeding dish (100 × 70 × 75 mm).…”
Section: Methodsmentioning
confidence: 99%
“…However in contrast, glucocorticoids do not appear to play a role in the plasticity of boldness of rainbow trout ( Oncorhynchus mykiss ) in the context of hunger and predation (Thomson et al, 2012). In European starlings ( Sturnus vulgaris ), a previous study found that a stress response immediately preceeding exposure to a novel object increases the frequency of neophobic responses in European starlings (de Bruijn & Romero, 2020). This suggests that stress exerts permissive actions on neophobia, in that it can alter how an individual responds to novelty (Sapolsky et al, 2000; Vera et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sparrows saw each object once. These objects were based on objects shown to elicit delayed approach and feeding in another songbird species [32], but altered slightly to share fewer common features (e.g. red colour) that might incidentally target ecologically relevant cognitive biases [33].…”
Section: (C) Novel Object Exposure Proceduresmentioning
confidence: 99%